ELABELA: A Hormone Essential for Heart Development Signals via the Apelin Receptor - Chng, Serene C.; Ho, Lena; Tian, Jing; Reversade, Bruno (Developmental cell, 2013)
We report here the discovery and characterization of a gene, ELABELA (ELA), encoding a conserved hormone of 32 amino acids. Present in human embryonic stem cells, ELA is expressed at the onset of zebrafish zygotic transcription and is ubiquitous in the naive ectodermal cells of the embryo. Using zinc-finger-nuclease-mediated gene inactivation in zebrafish, we created an allelic series of ela mutants. ela null embryos have impaired endoderm differentiation potential marked by reduced gata5 and sox17 expression. Loss of Ela causes embryos to develop with a rudimentary heart or no heart at all, surprisingly phenocopying the loss of the apelin receptor (aplnr), which we show serves as Ela's cognate G protein-coupled receptor. Our results reveal the existence of a peptide hormone, ELA, which, together with APLNR, forms an essential signaling axis for early cardiovascular development. [Display omitted] •ELA is an unannotated hormone present in hESCs and during embryogenesis•ela knockout zebrafish have endoderm defects and subsequent cardiac malformation•ela null embryos phenocopy apelin receptor (aplnr) mutant fish•Ela, not Apelin, is the earliest ligand for Aplnr during cardiovascular development Chng, Ho, et al. find that a seemingly noncoding mRNA actually produces a small peptide ligand for the apelin receptor (Aplnr). The zebrafish knockout of this ligand phenocopies the endoderm defects and cardiac dysgenesis seen in aplnr mutants. These results redefine an essential signaling axis for early cardiovascular development.